2015
DOI: 10.1049/iet-pel.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Temperature–humidity–bias testing on insulated‐gate bipolartransistor modules – failure modes and acceleration due to high voltage

Abstract: The temperature-humidity-bias (THB) test is the standard for accelerated stress testing with respect to corrosion and other humidity driven degradation mechanisms. Usually, 1000 h tests at 85°C and 85% relative humidity are used to predict up to 25 years of operation. The bias is usually limited to 80 V in order to fulfil the respective standards. Nevertheless, THB tests on 1700 V insulated-gate bipolar transistor (IGBT)-modules have shown that higher bias is a more severe test condition. The failure analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…• insulation degradation in the DC-link busbars/laminates, but above all of the DC terminals and busbars of power modules, which leads to short-circuit failure and with that often to a damage of modules connected to the same DC link • a reduction of the blocking capability of the power semiconductors due to electrochemical migration and aluminum corrosion, which was demonstrated by [43] under the combined influence of 85% relative humidity, a temperature of 85 • C and voltages above 65% of the nominal blocking voltage, and for which the occurrence even at lower humidity, temperature and voltage-stress levels is subject of further investigations…”
Section: Humidity and Condensationmentioning
confidence: 99%
“…• insulation degradation in the DC-link busbars/laminates, but above all of the DC terminals and busbars of power modules, which leads to short-circuit failure and with that often to a damage of modules connected to the same DC link • a reduction of the blocking capability of the power semiconductors due to electrochemical migration and aluminum corrosion, which was demonstrated by [43] under the combined influence of 85% relative humidity, a temperature of 85 • C and voltages above 65% of the nominal blocking voltage, and for which the occurrence even at lower humidity, temperature and voltage-stress levels is subject of further investigations…”
Section: Humidity and Condensationmentioning
confidence: 99%
“…These wires can become detached (lifted-off) during power cycling due to temperature stresses. From early failure when Bond wire lift-off one bond wire is lifted off to almost 65% of the wires lifted off, the IGBT is still able to function, albeit with a significantly increased risk of total failure [12]. Voltage drop across the bond wires increases as bond wires come adrift because of the increased load current passing through the remaining wires.…”
Section: A Topology Of Interestmentioning
confidence: 99%
“…As an alternative to a physical sensor, several methods have been presented in the literature to estimate junction temperature, , by monitoring certain electrical parameters. These methods are either based on direct measurement or data-driven methods as summarized in Fig 2 [10][11][12]. The direct method is not widely used due to the high implementation costs and the requirement to access the inside of the module.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the on-state collectoremitter voltage V CE,on is a good failure indicator of BWLO [9]. However, this parameter is affected by temperature changes and, hence, it can be cause by both BWLO and SF.…”
Section: Introductionmentioning
confidence: 99%
“…These can be detected with different methods before a complete damage to the component has occurred. Temperature swings are the cause of a not uniform expansion of the different materials of IGBT's and the resulting shear stresses potentially lead to fatigue [9]. The bonded area is where the bond wire foot is connected to the metal chip.…”
Section: Introductionmentioning
confidence: 99%